Herbal medicine for asymptomatic hyperuricemia: a systematic review and network meta-analysis - Min, Ye; Xiao, Fengqin; Zhou, Ling; Fan, Meng; Luo, Jinli; Zhao, Linhua (Frontiers in Pharmacology, 2025)
BackgroundThere is still controversy in the medical community about whether asymptomatic hyperuricemia (AH) requires drug treatment. Herbal medicines (HM) are considered a potential intervention for the treatment of hyperuricemia.ObjectivesThis study aimed to investigate the efficacy and safety of HM for asymptomatic HUA.Materials and MethodsA Bayesian network meta-analysis was conducted for patients with asymptomatic HUA in randomized controlled trials identified in PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang database, China Biomedical Database (CBM), and China Science and Technology Journal Database (VIP) were searched from their inception to 1 Jan 2025. Outcomes included the serum uric acid (SUA), secondary outcomes (TC, TG, HDL or HDL-C, LDL or LDL-C, and traditional Chinese medicine symptom scores), and adverse events. This study was registered in PROSPERO (CRD42024459357).ResultsAll evaluated HM formulations except Lily Plantago Seed tea demonstrated significant SUA reduction versus non drug therapy (NDT), achieving effect sizes spanning from -197.48 (95% CI −249.88 to −145.56) to −14.6 (95% CI −62.09 to 33.31). Probabilistic ranking identified Xuezhikang capsule as the most effective agent for SUA reduction (98.7%), with concurrent improvements in lipid profiles including TC, TG, and HDL levels. Therapeutic benefits extended to TCM symptom scores across all interventions (OR range 3.15–28.44), suggesting broader treatment potential for HUA management. No serious adverse events were documented throughout the trials.ConclusionHM interventions demonstrate potential efficacy in managing AH, showing significant reductions in SUA levels alongside beneficial effects on lipid profile modulation and TCM symptom alleviation. While these findings suggest therapeutic promise, the preliminary nature of the evidence necessitates rigorous validation through methodologically robust clinical trials.Systematic Review Registrationidentifier CRD42024459357.